Application of Response Surface Methodology to Optimize the Extracting Process of Molybdenum from Nickel Molybdenum Ore - Yang, Li; Yan, Qinghua; Wang, Qing; Zhang, Huirong; Zhang, Jianwei; Niu, Liyuan (Asian Journal of Chemistry, 2012)
The extraction of molybdenum was researched in order to find the effective recovery process. Through response surface methodology, the optimum condition was determined as follows: roasting temperature, 670 ºC; roasting time, 1.70 h; NaOH concentration, 60 %; liquid solid radio, 2. The yield of molybdenum was as high as 3.82 %.